The media and cultural productions in the context of the “Third Chimurenga” in Zimbabwe, 2000 to 2005 - Pasirayi, P (2016)
This thesis explores the role of the media in a "hybrid regime". Taking post-2000 Zimbabwe as a "hybrid regime" in flux over time, the thesis explores the media policies and strategies deployed by the ruling Zimbabwe African National Union - Patriotic Front (ZANU-PF) party in the context of the "revolutionary" seizure of white-owned farms in Zimbabwe in the early 2000s, what became known as the "Third Chimurenga". I examine how the ZANU (PF) media strategy was developed under the newly created Ministry/Department of Information and Publicity in line with the hegemonic ambitions and legitimation needs of the hybrid system that the party built during this period. Through this, the thesis exposes the shortcomings in the literature on hybrid regimes and a Zimbabweanist scholarly literature on the media and 'patriotic history', which both overly emphasise the formal media, and argues for a much deeper understanding of the role of the 'non-traditional' media and political practices that are historically and culturally constituted in the survival or persistence of these regimes. By showing the importance of history and culture in practices of regime legitimation and survival, the thesis challenges much of the assumptions within the literature on hybrid regimes which is largely quantitative and electoralist in approach. This thesis explores: i) the means and mechanisms of media control in a hybrid regime; ii) the tensions and contradictions that characterise a hybrid media system; iii) the role of the media in legitimacy construction, specifically how journalists framed events, and; iv) the role of the 'non-traditional' media or the forms of media drawn from history and culture in regime legitimation and survival. The thesis is based on interviews with ZANU (PF) elites, senior government officials, journalists, artists and a media content analysis as well as a variety of political actors in Murewa, a particularly violent and contested district in Zimbabwe.